STRATEGI DINAS KETENAGAKERJAAN DALAM MENGELOLA LAYANAN INFORMASI PASAR KERJA DI KABUPATEN BEKASI - Nur Aeni, Intan; Aditya, Indra; Febriantin, Kariena (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The high unemployment rate in Bekasi Regency indicates that labor market information services are not yet optimal, which is influenced by low vacancy reporting from companies, information gaps between job seekers and employers, and an increasing workforce. This study aims to analyze the strategies of the Bekasi Regency Manpower Office in managing labor market information services, assess the effectiveness of their implementation, and identify supporting and inhibiting factors. This study uses a qualitative approach with a case study type, data obtained through observation, interviews, and documentation studies, then analyzed using pattern matching techniques. Through a social constructivism paradigm, this study attempts to explore how the meaning, practices, and strategies of services are formed through social interactions between stakeholders. The results show that the Manpower Office's strategies have been developed in line with national and regional policies, with a focus on integrating manual and digital services. However, implementation is still hampered by limited human resources, a lack of cross-sector collaboration, and low digital literacy among job seekers. Innovations such as PasKerSquad and the use of the SIP-Kerja application have expanded the reach of information, although they have not been able to overcome bureaucratic barriers and low vacancy reporting from the industrial sector. This finding emphasizes the importance of an integrated, collaboration-based strategy to improve the effectiveness of labor market information services in Bekasi Regency